2023
DOI: 10.3390/pathogens12020329
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Immunity in the Pathogenesis of SARS-CoV-2 Infection and in the Protection Generated by COVID-19 Vaccines in Different Age Groups

Abstract: This study aims to review the available data regarding the central role of immunity in combating SARS-CoV-2 infection and in the generation of protection by vaccination against COVID-19 in different age groups. Physiologically, the immune response and the components involved in it are variable, both functionally and quantitatively, in neonates, infants, children, adolescents, and adults. These immunological differences are mirrored during COVID-19 infection and in the post-vaccination period. The outcome of SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 214 publications
0
5
0
Order By: Relevance
“…The trimeric S protein is a prominent immunological component of the virion surface and plays a crucial role in SARS-CoV-2 binding and entry to the host cell, mediating the interaction of the virus with the cellular receptor angiotensin-converting enzyme 2 (ACE2) and the subsequent fusion of the virus envelope with the host cell membrane. It has been clearly established that the production of S-specific antibodies that can neutralize the virus is crucial to confer protection against SARS-CoV-2 infection [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The trimeric S protein is a prominent immunological component of the virion surface and plays a crucial role in SARS-CoV-2 binding and entry to the host cell, mediating the interaction of the virus with the cellular receptor angiotensin-converting enzyme 2 (ACE2) and the subsequent fusion of the virus envelope with the host cell membrane. It has been clearly established that the production of S-specific antibodies that can neutralize the virus is crucial to confer protection against SARS-CoV-2 infection [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poor outcome could be determined by a declining immune system less able to clear the virus, but lung tissue damage in severe cases could also be caused by an exaggerated immune response, rather than damage inflicted by the virus itself [39][40][41][42][43]. Consequently, immunocompromised patients may be protected from this type of hyper inflammation [37,44,45]. We found that chronic use of antibiotics or dexamethason medication was associated with increased risk of death.…”
Section: Interpretation Of Results and Comparison To Literaturementioning
confidence: 99%
“…The median age of the severe/critical cases in this study was 77 (68-84) years, which was signi cantly higher than 65 (51-77) years for the ordinary cases. Furthermore, elderly individuals are more likely to experience complications, another risk for patients with COVID-19 [25] .…”
Section: Discussionmentioning
confidence: 99%